EEG-Based Analysis of Concentration with Shooting Accuracy and Precision in Archery Athletes: A Quantitative Correlational Study - Ainun Rahmansyah Gaffar; Pringgo Widyo Laksono; Bambang Suhardi; Rahmaniyah Dwi Astuti; Minoru Sasaki (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Archery performance as a precision sport is determined by a complex interaction between psychological and physiological factors. Concentration, as a crucial factor, can be objectively measured through electroencephalography (EEG) by detecting beta waves. However, current coaching practices disproportionately emphasize physical aspects while systematically ignoring concentration as a crucial psychological factor. Generally, studies assess performance through aggregate scores without distinguishing between two fundamental dimensions: accuracy and precision. This study aims to analyze the relationship between concentration levels measured through beta band power activity using EEG and shooting performance in archery athletes, focusing on shooting accuracy and shooting precision. This study offers empirical contributions about the relationship between concentration and two dimensions of shooting performance, develops a methodological validation that integrates EEG monitoring with smart bow technology, and establishes a practical foundation for developing concentration-based training programs in archery. The research subjects consisted of 12 novice archery athletes. EEG data were acquired with electrodes positioned at AF7 and AF8, monitoring beta band power during shot execution. Pearson’s correlation was used to analyze the relationship. The results showed a shot accuracy with an average score of 131.17, while precision showed an average SRD of 11.00 cm. Beta band power had a mean of 39.18 µV². Correlation analysis revealed a non-significant positive relationship between beta power and accuracy (r = 0.145, p = 0.652), as well as a non-significant negative relationship with precision (r = -0.327, p = 0.300). Study findings show that beta wave activity alone does not serve as a significant predictor of shooting performance in novice archers. However, the differential correlation pattern (positive for accuracy, negative for precision) confirms that these two dimensions are influenced by different psychophysiological mechanisms.